Live (stained) benthic foraminifera from the West-Gironde Mud Patch (Bay of Biscay, NE Atlantic): Assessing the reliability of bio-indicators in a complex shelf sedimentary unit. (1st January 2022) - Fontanier, C.; Deflandre, B.; Rigaud, S.; Mamo, B.; Dubosq, N.; Lamarque, B.; Langlet, D.; Schmidt, S.; Lebleu, P.; Poirier, D.; Cordier, M.A.; Grémare, A.
Abstract: Live (Rose Bengal stained) shelf foraminiferal faunas have been studied at seven stations located along a shore-open ocean transect between 39 and 69-m depth in the West-Gironde Mud Patch (WGMP) (Bay of Biscay, NE Atlantic) to understand how complex environmental conditions (e.g., organic matter, oxygenation, sedimentary facies) control their ecological patterns (i.e., diversity, faunal composition, standing stock, and microhabitats). To do so, the WGMP was sampled in August 2017, at the end of the succession of phytoplankton blooms occurring in spring and summer. This morpho-sedimentary unit is bathed by well-oxygenated bottom waters and characterized by clay-silt facies containing variably degraded phytodetritus and traces of terrestrial organic matter. Oxygen penetration depth within the sediment is less than 7 ± 3 mm, indicating efficient organic matter in-sediment mineralization by aerobic respiration. Foraminiferal richness (S) presents relatively moderate values ranging between 15 and 35 taxa. According to Shannon Index H', foraminiferal diversity tends to increase with water depth. Accordingly, the relative contribution of Eggerelloides scaber, the dominant foraminiferal species at all stations, decreases with increased depth and decreased proximity to the coast. The shallowest station (Station 1, 39 m), closest to the shore, is characterised by E. scaber, Quinqueloculina laevigata and Ammonia beccarii, species typical of inner-shelf environments constrained by high-energy hydrodynamics and river discharge. Surficial sediments at Station 1 constitute of winnowed sands depleted in organic carbon. Towards the centre of the WGMP, where clay-silt facies contain variably degraded marine phytodetritus and terrestrial organic compounds, foraminiferal faunas are characterized by Bulimina aculeata, Ammonia falsobeccarrii, Nouria polymorphinoides and Nonionoides turgidus . Yet E. scaber remains the most dominant taxon. Deeper stations (>55 m depth) located at the distal part of the mud patch are dominated by B. aculeata, A. falsobeccarrii, N. polymorphinoides and E. scaber. Accompanying these taxa are Bulimina marginata, Rectuvigerina phlegeri, Nonion faba and Paracassidulina neocarinata, which are typical of mid- and outer-shelf ecosystems enriched in sedimentary organic matter. Highlights: For the first time, living benthic foraminifera are studied in the WGMP. Foraminiferal diversity tends to increase with water depth along the mud patch. Hydro-sedimentary processes and food availability control foraminiferal faunas. A foraminiferal continuum exists through the WGMP and the Grande Vasière.